OPPORTUNITIES AND CHALLENGES OF USING ARTIFICIAL INTELLIGENCE IN LIBRARY AND INFORMATION ACTIVITIES (Web of Teachers: Inderscience Research, 2026)
This article analyzes the use of artificial intelligence technologies in information and library activities, their advantages and problems. The role of artificial intelligence in improving library services, its importance in providing users with fast and high-quality services is highlighted on a scientific basis. It is also recommended to improve the use of artificial intelligence in information and library institutions of the Republic of Uzbekistan, adapting it to our mentality.